Benefits on the Margin : Observations on Marginal Benefit Incidence - Younger, Stephen D. (Washington, DC: World Bank, 2014)
Benefit incidence analysis has become a popular tool over the past decade, especially for researchers at the World Bank. Despite or perhaps because of the popularity of this method, recent research has pointed out many of its limitations. One of the most common criticisms of benefit incidence analysis is that its description of average participation rates is not necessarily useful in guiding marginal changes in public spending policies. This article considers a variety of methods for analyzing the marginal benefit incidence of policy changes. A key conceptual point is that despite the fact that the various methods measure marginal incidence, they do not measure the same thing nor are they intended to do so. There are many possible policy changes and thus many margins of interest. Each method captures one of these and so is of interest for some analyses and inappropriate for others. Empirically, the precision of the methods differs substantially, with those relying on differenced data or aggregations of households yielding standard errors that are quite large relative to the estimated shares.